2016
DOI: 10.1016/j.dendro.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variability of stone pine ( Pinus pinea L.) growth response to climate across the Iberian Peninsula

Abstract: Climate warming and increasing aridity have impacted diverse ecosystems in the Mediterranean region since at least the 1970s. Pinus pinea L. has significant environmental and socio-economic importance for the Iberian Peninsula, so a detailed understanding of its response to climate change is necessary to predict its status under future climatic conditions. However, variability of climate and uncertainties in dendroclimatological approach complicate the understanding of forest growth dynamics. We use an ensembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 67 publications
2
12
0
3
Order By: Relevance
“…This is consistent with the change in temperature ( Figure 3) and SPEI trends of the study area and intensified spring droughts in the central Himalaya during recent decades [115]. Thus, increased drought might have caused the divergence in growth-climate relationships as observed in other studies [53,143,144], with Abies spectabilis trees showing growth plasticity towards the changing environment as other coniferous species do (e.g., [46,48,133,145]). Obviously, this potential adaptation contributed to the rather low responsiveness of the Rolwaling treeline to climate warming [73], and may be crucial for its future sensitivity to climate change.…”
Section: Changing Long-term Tree Growth-climate Relationships (The Ensupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with the change in temperature ( Figure 3) and SPEI trends of the study area and intensified spring droughts in the central Himalaya during recent decades [115]. Thus, increased drought might have caused the divergence in growth-climate relationships as observed in other studies [53,143,144], with Abies spectabilis trees showing growth plasticity towards the changing environment as other coniferous species do (e.g., [46,48,133,145]). Obviously, this potential adaptation contributed to the rather low responsiveness of the Rolwaling treeline to climate warming [73], and may be crucial for its future sensitivity to climate change.…”
Section: Changing Long-term Tree Growth-climate Relationships (The Ensupporting
confidence: 89%
“…Thus, the increasing data quality could play a certain role regarding more stable tree growth-climate relationships during recent decades [59]. However, CRU data are widely used in dendroclimatological studies (e.g., [106,133]), also in mountain regions [54,127,134,135] including the Himalaya [10,29,58,59,136] and their use is recommended for regions with sparse cover of stations despite certain limitations [137].…”
Section: Changing Long-term Tree Growth-climate Relationships (The Enmentioning
confidence: 99%
“…The resulting reaction norms were strongly influenced by the sites. Indeed, our study steps in the direction that tree ring longitudinal phenotypic plasticity should be seen as a plastic trait in itself, varying spatially (De Luis et al 2013; Natalini et al 2016), varying with long-term trends such as global warming (Natalini et al 2016), and varying with the level of competition between neighboring trees in wet years (Carnwath and Nelson 2016). Growth recovery, the ability for trees to produce large rings the years following a drought event, is also site-dependent (Gazol et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the interdependence of increasing temperatures and decreasing water availability, Sánchez-Salguero et al 2015showed that growth is more sensitive to drought than to temperature in several Mediterranean species, which is in accordance with the findings by Calama et al (2019). Understanding the effects of climate change on the ecology of Pinus pinea forests can help to assess the adaptive capacity of the species, and develop management programs aimed to ensure the conservation of its populations (Natalini et al 2016).…”
Section: Introductionmentioning
confidence: 61%
“…Climate change impacts on stone pine in the Mediterranean can be aggravated in extreme drought years. Further, Natalini et al (2016) suggested that the Pinus pinea species has a plastic response to warmer and drier climates that can vary among populations, and some measure of such variability should be considered in long-term forecasts of vegetation dynamics. Akyol & Orucu (2019) found that the most important bioclimatic variables affecting the potential distribution of P. pinea are the minimum temperature of the coldest month (Bio6), annual precipitation (Bio12), and precipitation of the wettest quarter (Bio16); whereas, Serra Varela (2018) found that annual mean temperature (Bio1), temperature seasonality (Bio4), precipitation seasonality (Bio15), precipitation of the warmest quarter (Bio 18), and precipitation of the coldest quarter (Bio 19) are the main drivers of stone pine distribution.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%